Building a Community: Disability and Identity in the Qur’an - Staffan Bengtsson (Scandinavian Journal of Disability Research, 2018)
This article elaborates on disability and the Qur’an and accentuates how a grand narrative of moral codes held the community together and enforced a collective identity of the ummah, in which disability was interlaced with the shaping of an in-group grounded in a common set of values. This process of identity making in turn had implications for people with disabilities, since they could have trouble fulfilling religious requirements, something that was met with counter mechanisms of solidarity within the community of Muslim believers.